Effect of Osun River Heavy Metal Contamination on Testicular Function in Wistar Rats - Adunfe, Oluwatobi Oluseun (My University, 2025)
Introduction: The Osun River is prone to contamination from industrial, agricultural, and domestic activities, resulting in heavy metal pollution. Widespread contaminants such as lead, mercury, cadmium, and arsenic can build up in aquatic ecosystems, presenting serious health hazards to both wildlife and humans. Even at low concentrations, heavy metals are toxic, with the testes being particularly vulnerable given their essential functions in reproduction and hormone regulation. This study aims to examine the potential testicular damage resulting from prolonged exposure to heavy metal-contaminated Osun River water. Materials & Methods: Thirty adult male Wistar rats, averaging 160 g in weight, were randomly divided into six groups (A–F), with each group consisting of five rats. Group A functioned as the control, whereas groups B, C, and D were exposed to mercury (6.8 mg/kg), cyanide (25.8 mg/kg), and lead (47 mg/kg), respectively. Group E received a combination of two heavy metals (lead and mercury) and a toxic compound (cyanide), while group F was given unrestricted access to Osun River water. All substances were administered orally via an oral cannula for a duration of four weeks. Results: Statistical analysis revealed no significant differences among the groups exposed to mercury, cyanide, lead, and Osun River water. Toxic effects on the testes included disorganization of seminiferous tubules, altered spermatogenic cell arrangement, structural changes in the basal membrane, testicular stroma abnormalities, and reduced sperm count, motility, and viability. These effects were dose- and time-dependent, occurring even at low concentrations.
Keywords: Heavy metals; Osun river; Testicular damage; Toxic effects